PERANAN DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT PLN PEMBANGUNAN SUMATERA UTARA - WI LIAM; Sauh Hwee Teng (Akuntansi Prima, 2023)
PT PLN Pembangkitan Sumatera Utara Medan, by reason of the selection of research objects due to the decreased employee performance in the company. Employee performance is a condition that indicates whether or not the employee is doing the work. This decrease in performance can be caused by work discipline and career development which is less suitable with the background of education level as well as position in work resulting in the occurrence of errors and boredom in work, the employee who often use the absent as a reason for saturation in the work so that violation of company regulations . The theory used in this research is Human Resource Management. This study aims to analyze how the influence of work discipline and career development of employees at PT PLN Pembangkitan Sumatera Utara. The research method used is descriptive quantitative with the nature of the research is explanatory. The analytical method used is multiple regression with the population used as many as 154 employees. Determination of sample used is sample saturated with amount of sample 154 employees and 30 employees of branch of PT PLN Sektor Pembangkitan Medan for validity test. The results showed that work discipline and career development simultaneously and partially significant effect on employee performance at PT PLN Pembangkitan Sumatera Utara and the coefficient of determination is 71%. So it can be concluded in this study that the work discipline and career development simultaneously and partially significant effect on employee performance at PT PLN Pembangkitan North Sumatra.